Foreword of the Issue - ENYEDI, Delia (Studia Universitatis Babeș-Bolyai Dramatica, 2023)
Scholarly approaches to narration in performing arts and visual arts have focused on identifying an array of narrative structures driven by plot or characters. However, Mieke Bal’s seminal Narratology (1985) separates the study of “elements” (events, actors, places of the story) from “aspects” (presentation of those elements by means of the text). In Gerald Prince’s (1982) words this opposition arises in questions of “how” against questions of “what”, with an emphasis on the fact that the latter has garnered significantly more attention than the first. More recently, Daniel Punday (2003) proposed “corporeal narratology” as an interpretive method focusing on textual features of the human body in relation to the other narrative elements. In line with the Posthuman Paradigm, Punday’s “corporeal hermeneutics” contradicts the soul-body dualism approaching the body not as a mere prop, as an inanimate object but as a vital agent.